2017
DOI: 10.1002/cncr.30839
|View full text |Cite
|
Sign up to set email alerts
|

Cancer survivorship and opioid prescribing rates: A population‐based matched cohort study among individuals with and without a history of cancer

Abstract: This study demonstrates substantially higher opioid prescribing rates among cancer survivors, even long after attaining survivorship. This raises concerns about the diagnosis and management of chronic pain problems among survivors stemming from their cancer diagnosis or treatment. Cancer 2017;123:4286-4293. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
74
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 27 publications
4
74
0
Order By: Relevance
“…The American Cancer Society also reported substantially higher opioid prescribing rates among cancer survivors (1.22 times higher) than among their counterparts who have never had cancer. Interestingly, opioid use was prevalent even among survivors who were 10 or more years past their cancer diagnosis . In a recent study describing opioid prescription patterns among patients with cancer, an HNSCC diagnosis was associated with increased odds of opioid prescription and a larger prescription quantity than patients with lung or colon cancer .…”
Section: Discussionmentioning
confidence: 99%
“…The American Cancer Society also reported substantially higher opioid prescribing rates among cancer survivors (1.22 times higher) than among their counterparts who have never had cancer. Interestingly, opioid use was prevalent even among survivors who were 10 or more years past their cancer diagnosis . In a recent study describing opioid prescription patterns among patients with cancer, an HNSCC diagnosis was associated with increased odds of opioid prescription and a larger prescription quantity than patients with lung or colon cancer .…”
Section: Discussionmentioning
confidence: 99%
“…Chronic opioid use has become a significant public health issue in our country. Cancer survivors are a vulnerable population with significantly higher rates of reported opioid use, even a decade after attaining survivorship . Patients with head and neck cancer often suffer significant morbidity as a result of their underlying disease process as well as treatment sequelae.…”
Section: Discussionmentioning
confidence: 99%
“…As cancer survivors live longer, pain from other conditions becomes common . A study out of Canada found opioid prescribing to be 1.2 times higher among cancer survivors than matched controls . This coupled with evidence that opioids influence multiple well‐established cancer pathways such as immune suppression, cell proliferation, cell invasion, and angiogenesis, points to a need for clinical studies of the effects of chronic use on cancer outcomes in diverse population and across different cancers.…”
Section: Discussionmentioning
confidence: 99%